One nation Britain : history, the progressive tradition, and practical ideas for today's politicians - Carr, Richard, 1985- (Ashgate, 2014)
What is One Nation politics? What has it been, and what should be it be today? Since Ed Miliband's speech at the 2012 Labour Party Conference these questions have been much asked, but not so often clearly answered. Outlining the historical context, and offering suggestions for contemporary thinkers, this comprehensive overview shows how all three major UK political parties have made a significant contribution to the One Nation agenda over the past century and a half. Re-asserting the One Nation tradition inherent in interventionist liberals like Keynes and Lloyd George, it encourages us to l.